The Application of Multimodal Texts in On-line Education in the Times of the Covid-19 Pandemic – A Linguistic Analysis of Blogs - Joanna HARDUKIEWICZ-CHOJNOWSKA (Communications of International Proceedings, 2021)
The majority of texts created nowadays is multimodal, which means that verbal language included in such texts is accompanied by other modes of expression, for example images. In order to fully understand messages conveyed by multimodal texts, it is necessary to pay attention to all the modes, because all of them contribute to the overall meaning. Therefore, it is particularly relevant to teach young learners how to interact with multimodal content, both when it comes to its production and comprehension. One of the most useful tools that can be used to familiarize students with multimodality is the Internet, which in the period of the COVID-19 pandemic became a significant part of education and human interaction in general. This paper describes one type of multimodal Internet genres, namely blogs, in terms of their thematic, stylistic and compositional features. The research material for the study consists in blogs created by students as a part of their final assignment during the summer semester 2021, when lessons at Polish universities were still taking place on-line due to the pandemic. The study is summarized by a description of the results of a questionnaire completed by the students in order to evaluate their experience with blogs. The research reveals that blogs are multimodal texts whose value in teaching is undeniable. Creating blogs enables students to develop their reading and writing skills and improves their ability to work with multimodal texts, at the same time allowing them to display their creativity.
Keywords: multimodality; blog; genre; multimodal text